(untitled) (REMUNOM, 2026)
This article analyzes Public-Private Partnerships (PPPs) in basic education, focusing on the recent experience of the State of Minas Gerais, from the perspective of New Public Governance. The study is grounded in the understanding that PPPs have been incorporated as governance instruments to address fiscal constraints, historical infrastructure deficits, and growing demands for efficiency in the management of public educational services. Methodologically, the research adopts a qualitative and exploratory approach, based on bibliographic research and documentary analysis. The documentary corpus includes legislation, institutional documents, and official materials from the Government of Minas Gerais related to the School Infrastructure PPP, encompassing information on scope, projected investments, number of schools involved, and implementation stages. Data were analyzed through content analysis, structured around analytical categories related to governance, quality, legitimacy, and accountability. The findings indicate that PPPs in Minas Gerais primarily focus on non-pedagogical services, such as maintenance, conservation, and infrastructure management, while formally preserving the State’s responsibility for curriculum and pedagogical management. Nevertheless, the documentary analysis reveals significant challenges regarding regulation, contractual monitoring, transparency, and social participation, particularly due to contractual complexity and information asymmetry among stakeholders. The study concludes that, although PPPs may contribute to improving school infrastructure and expanding state operational capacity, their legitimacy and effectiveness depend on strengthening democratic control, accountability mechanisms, and social participation to ensure socially referenced quality public education.